Pharmacological evaluation of Hepatoprotective activity of Indian medicinal plants Cordia Myxa and Canscora diffusa on wistar albino rats - Supyar Singh; Vishal Gupta (International Journal of Tropical Medicines, 2024)
Two plants (Cordia myxa and Canscora diffusa), which were claimed to possess hepatoprotective activity, were selected. The Selected plants were authenticated by an expert botanist. In the current study, herbal extraction involving solvents of decreasing polarity (petroleum ether, ethyl acetate, and hydroalcoholic) was used to extract bioactive compounds from the plants of Cordia Myxa and Canscora diffusa in polyherbal preparations. A phytochemical evaluation was performed, including an acute toxicity study and hepatoprotective activity induced by CCl4 and Peracetamol. The current investigation showed that polyherbal formulations at doses of 100, 200, and 400 mg/kg significantly reduced the severity of CCl4-induced and paracetamol-induced liver damage. By activating metabolism, which leads to selective toxicity in liver cells and impairment of metabolic activity. In conclusion, both the extract and the prepared formulation had significant liver-protective effects. This is evident from the evaluation of several important biochemical parameters in selected experimental animals. These parameters, which are generally related to liver function and damage. There was a marked improvement in response to treatment. The results indicate that the formulation is effective in protecting liver cells from damage or facilitating recovery. Observed decrease in liver enzyme levels of ALT, AST and bilirubin. Indicates reduction in liver stress and injury. It also confirms the tested formula's beneficial effects on overall liver health. These findings highlight its potential therapeutic value in the management of liver disorders.
Keywords: Canscora diffusa; Cordia myxa; Hepatoprotective; Phytochemical evaluation; polyherbal Formulation